Ultrasound Characteristics of Calf Deep Vein Thrombosis and Residual Vein Obstruction After Low Molecular Weight Heparin Treatment. Issue 5 (November 2016) - Sartori, M.; Lessiani, G.; Favaretto, E.; Migliaccio, L.; Iotti, M.; Giusto, L.; Ghirarduzzi, A.; Palareti, G.; Cosmi, B.
Abstract : Objective/Background: Calf deep vein thrombosis (CDVT) is frequently found in symptomatic outpatients, but CDVT ultrasound diagnostic criteria are still debated. It has been proposed that only clots with ≥5 mm maximum diameter can be considered as CDVT. Aims: To assess clot diameters and characteristics of CDVT, and to assess the recanalization rate of CDVT after anticoagulant treatment. Methods: In a prospective, multicenter cohort study symptomatic outpatients in whom CDVT was diagnosed by ultrasound were enrolled. Posterior tibial, fibular, medial and lateral gastrocnemius, and soleal veins were compressed transversally over their entire length. Clot diameter was measured during maximum compression and ultrasound was repeated after 6 weeks of low molecular weight heparin treatment. Results: In 172 patients (age 70 ± 1 y, male 32%) CDVT was detected in 132 (76.7%) muscle veins only, and in 24 (14%) axial veins only, while 16 (9.3%) patients had both muscular and axial CDVT. A total of 212 clots were found with a diameter of 5.8 ± 1.8 mm (IQR 4.5–6.8 mm) with the 10th percentile being ≥3.5 mm. A cut off value of ≥5 mm had a sensitivity of 0.76 (95% CI 0.69–0.82), whereas a value of ≥3.5 mm had a sensitivity of 0.94 (95% CI 0.89–0.97). Recanalization (i.e. residual vein obstruction ≤2 mm) was found in 51% of patients and the recanalization rate was not correlated with clot diameter at enrolment (rho −0.128 p = 0.93) or with type of CDVT (axial vs. muscular thrombosis). Patients with significantly reduced mobility had lower probability of CDVT recanalization. Conclusion: A clot diameter ≥5 mm is found in only 76% of CDVT patients and a clot diameter ≥3.5 mm may be more appropriate as a threshold for CDVT. After 6 weeks of anticoagulant treatment, half of CDVT patients had recanalization and recanalization was not correlated with clot characteristics at enrolment, but with mobility of the patients.